Efeito da adição de Aniba Canelilla, Blueberry e Polifenol de chá verde sobre a viabilidade in vitro de espermatozóides de Búfalo (Bubalus Bubalis) resfriados a 5º C. - Veronica Alexandra Becerra Becerra (2017)
The increase of reactive oxygen species (ROS) generates oxidative stress, which causes harmful effects to spermatozoa in cooled, frozen and post thaw procedures. The use of non-enzymatic antioxidants in extenders, could preserve the spermatozoa from negative action of ROS during the cryopreservation process. The aim of this study was to determine appropriate concentrations of non-enzymatic antioxidants Aniba canelilla, blueberry and green tea polyphenol in the extender Tris with 10% LDL, and test their efficiency on spermatozoa viability and longevity in buffalo semen preserved at 5°C. This work was divided into two phases. Ejaculates of nine buffalo bulls were used to test each antioxidant. Samples of phase 1 and 2 were analyzed by CASA before refrigeration and every 24 hours after refrigeration until total sperm motility decreased to 10%. The functional plasma membrane integrity was analyzed by hypoosmotic swelling test in fresh semen, 24 and 48 hours in phase 1; 24 and 72 hours in phase 2. Additionally, samples of phase 2 were analyzed by acrosome integrity on fresh semen, 24 and 72 hours; and by flow cytometry to evaluated structural plasma membrane integrity and sperm chromatin integrity at 24 and 72 hours after cooling. The experimental design used was a randomized block, the data were analyzed by the least squares method using the PROC MIXED of program SAS - version 6.12. For variables that after transformation of data did not satisfy the homoscedasticity of variances, it was used the non-parametric Friedman test with the program InfoStat (2014). Differences were considered to be statistically significant when P0.05. In phase one it was determined the best concentration of Aniba canelilla (0,5; 5 or 50 µg/ml), blueberry (10, 50 e 100 µg/ml) and green tea polyphenol (0,05; 5 or 50 µg/ml) added to the extender Tris 10% LDL. The elected concentrations were for Aniba canelilla 50µg/ml, blueberry 50 µg/ml and green tea polyphenol 0,05ìg/ml based on results of spermatic kinetics (P0.05) and/or based on their innocuous results for buffalo spermatozoa. The addition of 50 ug/ml of green tea polyphenol to the extender Tris 10% LDL exerted negative consequences on motility, plasma membrane integrity and survival of sperm buffalo. In phase two the efficiency of the best concentrations of the antioxidants tested in phase one was compared. In phase 2 the extender Tris 10% LDL supplemented with Aniba canelilla 50 µg/ml lead to the improvement of spermatic kinetic parameters (P0.05) such as total motility (TM), PM, Rapid, VCL, VSL, VAP and BCF; besides preserving spermatic longevity in buffalo semen cooled at 5°C for a long period. Functional and structural plasma membrane integrity, acrosome integrity, chromatin integrity did not significantly differ between treatments. It is concluded that Aniba canelilla may be of considerable help for buffalo semen and for other species if the concentrations are adjusted to the extenders. More assessments of each substance are needed in order to obtain a gain in sperm preservation and protect them from oxidative stress without affecting fertility.